Law, Finance, and Firm Growth - Demirgüç-Kunt, Asli; Maksimovic, Vojislav (Journal of Finance, 1998)
We investigate how differences in legal and financial systems affect firms' use of external financing to fund growth. We show that in countries whose legal systems score high on an efficiency index, a greater proportion of firms use long‐term external financing. An active, though not necessarily large, stock market and a large banking sector are also associated with externally financed firm growth. The increased reliance on external financing occurs in part because established firms in countries with well‐functioning institutions have lower profit rates. Government subsidies to industry do not increase the proportion of firms relying on external financing.